2007
DOI: 10.1093/cvr/cvm081
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent activation of ER  lowers blood pressure and attenuates cardiac hypertrophy in ovariectomized spontaneously hypertensive rats

Abstract: Ligand-dependent activation of ERbeta confers blood pressure lowering effects in SHR that are superior to those of 17beta-estradiol or the ERalpha agonist 16alpha-LE2 and attenuates cardiac hypertrophy primarily by a reduction of cardiac afterload without promoting uterine growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 36 publications
1
49
0
1
Order By: Relevance
“…Indeed, basal arterial blood pressure increases more in ERβ −/− mice during aging than in age‐matched control mice 49. In addition, the pharmacological activation of ERβ leads to blood pressure lowering in spontaneously hypertensive rats with reduced myocardial hypertrophy 50. Arias‐Loza et al also show that both ERα and ERβ activation attenuates cardiovascular remodeling in aldosterone salt‐treated rats 51.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, basal arterial blood pressure increases more in ERβ −/− mice during aging than in age‐matched control mice 49. In addition, the pharmacological activation of ERβ leads to blood pressure lowering in spontaneously hypertensive rats with reduced myocardial hypertrophy 50. Arias‐Loza et al also show that both ERα and ERβ activation attenuates cardiovascular remodeling in aldosterone salt‐treated rats 51.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid signaling by estrogen also prevents aspects of atherosclerosis in cells from animal models (62). Several groups have shown that ER␤ mediates the ability of estrogen to prevent cardiac hypertrophy that results from G q ␣ signaling by angiotensin II (Ang II) (2), genetic hypertension (17), or pulmonary hypertension (27). We have shown that membrane ER␤ signaling prevents the activation of calcineurin by Ang II or endothelin-1 (43).…”
Section: Impact Of Membrane Er For Protection Against Cardiovascular mentioning
confidence: 99%
“…4 Furthermore, activation of ERβ improved nitric oxide-dependent vasorelaxation, increased cardiac output, and attenuated cardiac hypertrophy; however, this study did not determine whether these effects were peripherally or centrally mediated.…”
mentioning
confidence: 77%
“…3 Pharmacological studies supported these conclusions by demonstrating selective agonists of ERβ-reduced arterial pressure in ovariectomized spontaneously hypertensive rats under conditions in which ERα-selective agonists did not. 4 Furthermore, activation of ERβ improved nitric oxide-dependent vasorelaxation, increased cardiac output, and attenuated cardiac hypertrophy; however, this study did not determine whether these effects were peripherally or centrally mediated.…”
mentioning
confidence: 77%
See 1 more Smart Citation